The Role of Education and Training Towards Employee Performance Improvement at Jejawi District Office Ogan Komering Ilir District - Ahmad Yani Kosali (Journal of Sustainable Development Science, 2022)
A job can be done / done more quickly if the employee / employee understands the meaning of education and training. The aim of this research was to know the role of education and training in improving employee performance at the Head Office of Jejawi District, Ogan Komering Ilir Regency. Nowadays, education and training have become an inseparable part of human resources/employees so that every agency must implement this method. The method used in this research is a qualitative method, in which the researcher conducts research directly to the research object that has been determined in order to be able to see and observe directly the problems studied. The conclusion of this study is that the role of education and training in improving employee performance at the Jejawi sub-district office, Ogan Komering Ilir district, is quite good. This is evidenced by the ability of employees to understand their duties and provide good service to the community.